Exploring the Application of Green Chemistry in Textile Heritage Conservation and Restoration with the Example of Buzi - Zihan, Xu; Lim, Chen Kim; Jia, Lyu; Ahmed, Minhaz Farid; Tan , Kian Lam (Journal of Ecohumanism, 2025)
Textile conservation and restoration is challenged by environmental damage and the inadequacy of traditional methods, especially for precious textile heritage such as Buzi from the Ming and Qing dynasties. This study aimed to explore the application of green chemistry in textile heritage conservation and restoration by cleaning textiles gently and effectively, and also reinforcing, mending, and dyeing while reducing environmental impacts. It was found that methods such as green cleaning agents were valid in removing stains from Buzi, as well as maintained their texture and color integrity, and were environmentally friendly. Green chemistry methods show great potential to conserve heritage and reduce the environmental burden effectively. Green chemistry has a promising future in textile heritage conservation and restoration, contributing to the sustainable conservation and preservation of textile heritage.